Cocaine impairs working and reference components of spatial memory in laboratory rats - Quirk, Phillip L., author; Avery, David D., advisor; Richards, Bill, advisor; Clay, Colin M., committee member; Bennett, Thomas L., committee member; Oetting, Gene, committee member (Colorado State University. Libraries, 1999)
In the United States the illegal use of cocaine is prevalent across socioeconomic levels and age groups. Since cocaine has been shown to cause significant disruptions of normal functioning in many bodily systems and causes deficits in cognitive functions such as memory, it is important to investigate the extent of these effects in systematic, controlled studies. Because it is not ethically possible to do this using human subjects, an animal model of chronic cocaine abuse has been employed to determine the effects of daily cocaine exposure on reference and working memory. Forty-eight male Sprague-Dawley rats were given daily injections of saline, 20mg/kg cocaine, or40mg/kg cocaine and their performance swimming in a Morris water maze was assessed. Animals were required to locate a hidden platform either without prior experience in the maze, or after four days of cued trials training in the maze prior to being required to find the hidden platform. Animals in all treatment groups learned to locate the hidden platform, but the efficiency with which they learned was affected by cocaine. A dose-dependent increase in escape latency was observed in the animals that received cued trial training prior to being required to locate the hidden platform. Cocaine also caused an increase in escape latency in animals that were not trained on cued trials prior to hidden platform trials. This increase, however, was not dose dependent. Furthermore, the animals receiving cued trial training prior to hidden trial training had shorter escape latencies than animals that had no initial cued trial training regardless of treatment condition. The results of this investigation indicate that cocaine produces memory deficits in laboratory rats, but that the animals are still capable of learning. In addition, it is apparent that the amnestic effect of cocaine is determined, in part, by the learning history of the subject.
Keywords: psychobiology; toxicology; neurology; cognitive therapy; neurosciences; cognitive psychology